Potential Of Cananga odorata AND Cymbopogon citratus Essential Oils To Inhibit The In Vitro Growth Of Staphylococcus aureus ATCC 25923 and Candida albicans ATCC 10231 - Kurnilia, Kadek Wegi; Sudirga, Sang Ketut; Ramona, Yan (Metamorfosa: Journal of Biological Sciences, 2020)
Cananga odorata and Cymbopogon citratus are two plant species producing inhibitory compounds in their essential oils. In our current research, the potential of their essential oils to inhibit the growth of Staphylococcus aureus and Candida albicans were investigated. MIC (Minimum Inhibitory Concentration) values of mixture of those essential oils with a ratio of 1:1 on those microbes were also assayed. Bioassays were conducted on Nutrient Agar (NA) or Potato Dextrose Agar (PDA) medium added with various ratios of the two plant species essential oils. Medium added with sterile distilled water served as control. The data obtained were analyzed quantitatively with SPSS software for Windows version 22. When significant different at p<0.05 was indicated, the analysis was continued with Duncan's multiple range test. The result showed that all treatment of essential oils applied effectively eliminated the growth of S.aureus . C.albicans appeared to be relatively resistant to 100% of C.odorata essential oil. Elimination of C.albicans was observed when the essential oil of C.odorata was combined with that of C.citratus . When compared to control, all ratios of essential oils treatments were statistically significant (p<0.05). The MIC values of essential oil mixture a ratio of 1:1 on S.aureus and C.albicans were 0,1% and 2,6% respectively.   Keyword s : essential oil, Cananga odorata , Cymbopogon citratus , Staphylococcus aureus , Candida albicans